Analysis on WBS-RBS Based Smart Bank Credit Risk - Xiaojing Dong (Forest Chemicals Review)
After the outbreak of the subprime crisis in the United States, many countries have dealt with the commercial bank credit risk problem. They have taken a series of response measures. It is pivotal to manage prudent risk. It is the theoretical cornerstone of vital parts to ensure that the commercial banks could develop forward steadily, in particular, especially for customers, itself themselves against risk management ability is weak, and more Add to need to be more prudent risk control management of good science, including the main research content of the project mainly involves with code for the postal savings bank of China commercial bank credit risk management from prudent investigation before loan, loan review, post-loan monitoring patrol from three large horizontal level, loans for individuals, small and medium-sized enterprises, special loan for poverty alleviation and other three small longitudinal level for certain Quantitative analysis reveals that China’s banking system in the face of dealing with three different types of loans at three different levels of management countermeasures, there are corresponding supporting policies and need to improve the problem of measures.